2006
DOI: 10.1016/j.cemconres.2006.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Reactive pozzolanas from rice husk ash: An alternative to cement for rural housing

Abstract: This paper discusses the properties of rice husk ash samples produced from different types of field ovens to compare the performance of the ovens and to identify the most feasible method to produce a reactive pozzolana as an alternative to cement for building applications requiring lower strengths. Different types of ashes are produced and long-term strength of rice husk ash pozzolanas with lime or cement is investigated to suggest a sustainable affordable option in rural building applications, especially for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
6

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(58 citation statements)
references
References 10 publications
0
45
0
6
Order By: Relevance
“…A number of research studies on fiber-reinforced soils have recently been carried out through triaxial tests, unconfined compression tests, CBR tests, direct shear tests, and tensile and flexural strength tests (Freitag, 1986;Maher and Gray, 1990;Al-Refeai, 1991;Fatani et al, 1991;Maher and Ho, 1994;Ranjan et al, 1996;Nataraj and McManis, 1997;Consoli et al, 1998Consoli et al, , 2002Consoli et al, , 2005Santoni et al, 2001;Kumar et al, 2005;Casagrande et al, 2006Casagrande et al, , 2007aCasagrande et al, , 2007bKim et al, 2008;Park, 2008;Bera et al, 2009;Fatahi et al, 2012;Divya et al, 2014;Li et al, 2014;Anggraini et al, 2014;Botero et al, 2015). One of the primary advantages of randomly distributed fibers is the absence of potential planes of weakness that can develop parallel to oriented reinforcement (Maher and Gray, 1990).…”
Section: Fiber-reinforced Soilmentioning
confidence: 99%
“…A number of research studies on fiber-reinforced soils have recently been carried out through triaxial tests, unconfined compression tests, CBR tests, direct shear tests, and tensile and flexural strength tests (Freitag, 1986;Maher and Gray, 1990;Al-Refeai, 1991;Fatani et al, 1991;Maher and Ho, 1994;Ranjan et al, 1996;Nataraj and McManis, 1997;Consoli et al, 1998Consoli et al, , 2002Consoli et al, , 2005Santoni et al, 2001;Kumar et al, 2005;Casagrande et al, 2006Casagrande et al, , 2007aCasagrande et al, , 2007bKim et al, 2008;Park, 2008;Bera et al, 2009;Fatahi et al, 2012;Divya et al, 2014;Li et al, 2014;Anggraini et al, 2014;Botero et al, 2015). One of the primary advantages of randomly distributed fibers is the absence of potential planes of weakness that can develop parallel to oriented reinforcement (Maher and Gray, 1990).…”
Section: Fiber-reinforced Soilmentioning
confidence: 99%
“…O uso da cinza de casca de arroz (CCA) em concreto foi patenteado no ano de 1924 e, após 1972, muitos pesquisadores concentraram-se na utilização da CCA derivada de queima não controlada (NAIR et al, 2006). A partir daí, diversas pesquisas têm sido realizadas com o uso da CCA em matrizes cimentícias, tanto para cinzas produzidas com queima controlada, quanto aquela à base de cinza de casca de arroz residual, obtida no processo de beneficiamento de arroz.…”
unclassified
“…The amorphicity favors the pozzolanic activity of the RHA according to NAIR et al (2006). For the SDBA (Figure 3), it was observed that there is presence of crystalline phases, especially the quartz (SiO 2 ) and calcium carbonate (CaCO 3 ).…”
Section: Characterization Of Raw Materialsmentioning
confidence: 97%